Legal Reform to Address the Regulatory Gap on Deepfakes as a Digital Manipulation Tool that Threatens Civil Rights Based on a Legal Philosophy Perspective - Yovid; I Made Juni Artawan; Zainal Arifin Hoesein (SULTAN ADAM: Jurnal Hukum dan Sosial, 2026)
Advances in artificial intelligence (AI) technology have given rise to deepfake technology, which is capable of realistically manipulating images, videos, and audio, thereby posing a potential threat to the civil rights of the public. The misuse of deepfakes can result in violations of the rights to privacy, personal identity, good name, reputation, and economic rights regarding one’s own image. The primary issue faced is the absence of specific regulations regarding deepfakes within the Indonesian legal system, resulting in a legal vacuum (rechtvacuum) and legal uncertainty (rechtsonzekerheid). This study aims to analyze the legal issues surrounding the use of deepfakes, examine the regulatory gaps in the Indonesian legal system, and formulate legal reforms based on a legal philosophy perspective. The research method employed is normative legal research using a statutory approach and a conceptual approach. The results of the study indicate that the provisions in the Electronic Information and Transactions Law, the Personal Data Protection Law, the Copyright Law, and the Civil Code have not been able to provide comprehensive protection against the misuse of deepfakes. Legal reform is necessary through the establishment of specific regulations governing definitions, legal liability, takedown mechanisms, and the restoration of victims’ rights to achieve justice, legal certainty, and public interest.